Blueprint for a macro-region: EU strategies for the Baltic Sea and Danube regions - Carsten Schymik (Stiftung Wissenschaft und Politik (SWP), 2011)
In October 2009, the European Union concluded its Baltic Sea Strategy, which has been followed in June 2011 by another strategy for the Danube region. The EU is thereby in the process of testing a new political concept for increasing territorial cohesion within the Union: the macro-region. The macro-region constitutes a territorially and functionally-defined cross-border region within the EU, in which a group of member states cooperate to achieve specific strategic objectives. If the model experiment in the Baltic Sea and Danube regions is successful, the macro-region could develop into a blueprint for a new operational level within the EU. Comparative analysis of the Baltic Sea and Danube strategies shows that it would still be premature to proclaim the macro-region as a new intermediary policy level within the EU. The model experiment, however, has definite development potential. Despite the rejection of any new laws, budget lines or institutions ("three no's"), the first macro-regions have been characterised by an increase in cooperation among core groups of member states, which could generate influence over the EU as a whole, without formally constituting a political operational level. This presents Germany's European policy, in particular, with special opportunities and challenges, because the Federal Republic is the sole member state that is incorporated into both macro-regions. It is also the only member state whose participation is principally handled by subnational actors, namely the federal states. Among other things, Germany should therefore use its current presidency of the Council of the Baltic Sea States to initiate an exchange of experiences across the entirety of Europe regarding the macro-region model experiment
Keywords: 320; Europäische Union; Mehrebenen-System